Validity of Enrichment Materials for the Mangifera Genus Inventory Booklet for the Biodiversity Concept in High School: Validitas Bahan Pengayaan Booklet Inventarisasi genus Mangifera Konsep Keanekaragaman Hayati di SMA - Zakiah, Nur; Mahrudin; Iriyanti, Riya (BIO-EDU: Jurnal Pendidikan Biologi, 2025)
Learning in the current era is learner centered, requiring teachers to prepare extensive knowledge and insight in learning so that it is easy to achieve learning objectives, namely by preparing enrichment materials that are in accordance with the times, such as Booklet. Booklet design with many interesting and colorful images, as well as with brief information, can be used as a means of increasing understanding of a material, especially on biodiversity material in high school. Inventorying the Mangifera genus is one of the information related to local potential that can be used in learning, for example the Mangifera genus in Sungai Landas Village. This study aims to describe the validity of Booklet enrichment materials. This type of research is the development (R & D) of Booklet using the Plomp model with 5 phases. The results showed that the validation test by 2 lecturers from Biology Education FKIP ULM Banjarmasin, and 1 biology teacher SMAN 1 Karang Intan Booklet overall the results of the category were very valid with a score of 90.70%.